Reaktualisasi Jihad Fî Sabîl Al-Lâh Dalam Konteks Kekinian Dan Keindonesiaan - Muhammad Chirzin (Ulumuna, 2006)
Some moslems perceive the concept of jihad simply on the perspective of political ideology. Jihad is understood as fight againts external enemies. This leads to the meaning of jihad as a struggle using the power of weapon (war) againts the enemy of Islam. This makes it contraproductive for Indonesian moslems who live in pluralistic society. Therefore, reinterpretation of the meaning of jihad is urgently needed to get a more contextual meaning in accordance with the Indonesian moslems circumtances. Refering to the classical literatures, the meaning of jihad, can be corrected to be more conceptual and practical. Jihad should contain a concept of collective struggle to overcome the actual problems faced by moslems such as economy, law, and education.